EzTrack—A Step‐by‐Step Guide to Behavior Tracking. Issue 10 (5th October 2021) - Pennington, Zachary T.; Diego, Keziah S.; Francisco, Taylor R.; LaBanca, Alexa R.; Lamsifer, Sophia I.; Liobimova, Olga; Shuman, Tristan; Cai, Denise J.
Abstract: Tracking animal behavior by video is one of the most common tasks in neuroscience. Previously, we have validated ezTrack, a free, flexible, and easy‐to‐use software for the analysis of animal behavior. ezTrack's Location Tracking Module can be used for the positional analysis of an individual animal and is applicable to a wide range of behavioral tasks. Separately, ezTrack's Freeze Analysis Module is designed for the analysis of defensive freezing behavior. ezTrack supports a range of desirable tools, including options for cropping and masking portions of the field of view, defining regions of interest, producing summary data for specified portions of time, algorithms to remove the influence of electrophysiology cables and other tethers, batch processing of multiple videos, and video down‐sampling. Moreover, ezTrack produces a range of interactive plots and visualizations to promote users' confidence in their results. In this protocols paper, we provide step‐by‐step instructions for the use of ezTrack, from tips for recording behavior to instructions for using the software for video analysis. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Software environment installation Basic Protocol 2 : Using the Location Tracking Module Basic Protocol 3 : Using the Freeze Analysis Module